The Role of Protein Modifications of T-Bet in Cytokine Production and Differentiation of T Helper Cells - Sera Oh; Eun Sook Hwang (Journal of Immunology Research)
T-Bet (T-box protein expressed in T cells, also called as TBX21) was originally cloned as a key transcription factor involved in the commitment of T helper (Th) cells to the Th1 lineage. T-Bet directly activates IFN-γ gene transcription and enhances development of Th1 cells. T-Bet simultaneously modulates IL-2 and Th2 cytokines in an IFN-γ-independent manner, resulting in an attenuation of Th2 cell development. Numerous studies have demonstrated that T-bet plays multiple roles in many subtypes of immune cells, including B cell, dendritic cells, natural killer (NK) cells, NK T cells, and innate lymphoid cells. Therefore, T-bet is crucial for the development and coordination of both innate and adaptive immune responses. To fulfill these multiple roles, T-bet undergoes several posttranslational protein modifications, such as phosphorylation at tyrosine, serine, and threonine residues, and ubiquitination at lysine residues, which affect lineage commitment during Th cell differentiation. This review presents a current overview of the progress made in understanding the roles of various types of T-bet protein modifications in the regulation of cytokine production during Th cell differentiation.